Peningkatan Keterampilan Guru Membuat LKPD BDR Melalui Kegiatan Workshop Di SMP Negeri 1 Umalulu Semester 1 Tahun Pelajaran 2020/2021 - Jakobis Daniel Mboeik (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
The research aims to improve the skills of teachers in making LKPD BDR through the implementation of workshop activities. The research subjects were 12 educators at SMPN 1 Umalulu. Technique, data collection, with observation sheets and documentation sheets. The analysis of the results of the research was carried out using comparative description techniques. Observation assessment of discussion activities on initial conditions obtained a value of 47.08 in the LESS criterion, to 69.38 in the ENOUGH criteria in the first cycle and 90.83 in the EXCELLENT criteria in the second cycle. The explanation regarding the classical teacher skill improvement in making LKPD in the initial condition is 50.38 in LESS qualification, in the first cycle it is 69.98 in the ENOUGH qualification and in the second cycle it is 84.85 in the qualification of BAIK. In terms of improving teacher skills in making BDR LPKD individually, in the first cycle there were 7 teachers 58.33% in the GOOD category, in the second cycle 12 teachers (100%) stated that their skills had increased in making BDR LKPD